Does increasing inequality threaten social stability? Evidence from the lab - Abigail Barr; Anna Hochleitner; Silvia Sonderegger (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2024)
We study the relationship between inequality and social instability. While the argument that inequality can be damaging for the cohesion of a society is well established, the empirical evidence is mixed. We use a novel approach to isolate the causal relationship running from inequality to social instability. We run a laboratory experiment in which two groups interact repeatedly and have an incentive to coordinate even though coordination comes at the cost of inter-group inequality. Then, we vary the extent of the inequality implied by coordination. Our results show that increasing inequality has a destabilising effect; the disadvantaged initiate the destabilisation; and a worsening of the absolute situation of the disadvantaged exacerbates the destabilising effect of increasing inequality. These findings are in line with a simple model incorporating inequality aversion and myopic best response. Finally, we show that history matters. People respond differently to the same level of current inequality depending on their past experiences. More specifically, a history of stability facilitates the re-emergence of coordination in more unequal environments, and a sudden increase in inequality is more destabilising than a gradual increase.
Keywords: C92; D01; D63; D74; 330; Collective decision making; Conflict and Revolutions; Inequality